A textual study of the passages containing plural forms related to the generic Name of God and to the Tetragrammaton in the Pentateuch - Oseka, Matthew (Vox Scripturae - Revista Teológica Internacional, 2016)
The present paper is focused on the textual study of the passages containing the plural forms touching the Divinity in the Hebrew Bible. Those passages, namely Genesis 1.26-27, 3.22, 11.7, 20.13, 35.7, Deuteronomy 4.7, 5.26(23) and 2 Samuel 7.23, were acting as a catalyst for profound theological analyses both Jewish and Christian. It was observed that the text of the plural forms touching the Divinity analysed in the present paper was stabile and no variants of the Hebrew text were evidenced except for Genesis 20.13 and 35.7 in the Samaritan Pentateuch. Furthermore, the aforementioned loci were examined in light of the ancient biblical translations and in view of the talmudic references which bear testimony to an early Jewish interpretation of them.